An integrative conservation and management strategy based on biological and cultural diversity assessment: A case study of Miaoling mountainous region, China - Xiaoqi Li; Jiaojiao Zhu; Xinyi Lyu; Yiyun Sun; Chuandong Tan; Bin Zhang; Paolo Tarolli; Qichi Yang (Ecological Indicators)
The Miaoling mountainous region, a typical karst landscape in Southwest China, is rich in biological resources and possesses an indigenous cultural heritage. However, ecological degradation and the encroachment of external cultures present significant threats to these areas, creating dual challenges to their biological and cultural integrity. To effectively protect the bio-cultural features in the Miaoling region, this study proposes a strategy for establishing a conservation framework based on the evaluation of bio-cultural diversity for protection. First, the four indicators of biodiversity and five indicators of cultural diversity were used to assess the value of bio-cultural diversity. Next, the Zonation model was integrated to identify priority zones. Finally, using these priority zones, a ’source − corridor − network’ strategy was developed. The results have revealed that nearly half of the region exhibits a lack of coordination between bio-cultural diversity. The priority conservation zones for bio-cultural diversity, which cover a total area of 2,286.76 km2, are located within small watershed and agroforestry ecosystems, displaying a fragmented distribution. Also, the conservation network encompasses 29 primary corridors, 76 secondary corridors, and 25 nodes. Based on that, a multi-stakeholder adaptive management framework has been proposed, emphasizing policy and financial support, community participation, and collaboration to integrate ecological protection with sustainable development. This study highlights the potential of bio-cultural diversity assessments in identifying priority zones and guiding strategic conservation planning in the karst mountainous regions.